The legacy of 9/11 : views from North America - Charron, Andrea; Moens, Alexander, 1959-; Roussel, Stéphane, 1964- (McGill-Queen's University Press, 2023)
"While 9/11 was understood at the time as a world-changing event in international relations, its uneven aftermath and the long-term effects for North America could not have been predicted. Twenty years later, The Legacy of 9/11 explores the political, economic, security and defence, and trade and border implications of the event. Written by a team of North American experts across many fields, the book foregrounds the fallout of 9/11 in Mexico and Canada as opposed to the more commonly discussed impact on the United States. Looking at the event and its aftermath through four lenses--ideas about North America; border, trade, and economics; security and society; and defence--contributors analyze the complex legacy of 9/11. Rather than serving as a catalyst to create an integrated, trilateral continent, 9/11 entrenched the North America we have today: three separate states with emphasis on two very different borders. From a reconsideration of internationalism, a rise in populism, and a shift in migration patterns to the interventions in Afghanistan and Iraq, The Legacy of 9/11 uncovers how successive North American governments reacted in surprising ways to the world-altering attack."--